Disrupting the center : a partnership approach to writing across the university - Hallman Martini, Rebecca (Utah State University Press, 2022)
"Analyzes and critiques one particular writing center's partnership-approach to collaboration with disciplinary faculty and upper administrators across the curriculum and offers writing centers a framework for responding to disruptive innovations in higher education"--